(untitled) (Journal of Humanitarian and Applied Sciences, 2022)
Translation and Arabization have played an effective scientific and civilized role throughout history. They have also played a key role for them in terms of linking the past with the present. The periods of great civilizations have been transmitted over the years thanks to its translation into the languages of different nations and its crossing into our diverse cultures to reach us today, and it enriches the various aspects of our contemporary life. The Western world is witnessing a remarkable development in the field of science and technology, so the Arabs need extensive and deep translation and Arabization processes for many new scientific terms. Because of the importance of this topic, and the close relationship between the success of translation and Arabization, is the extent of the language’s ability to develop, grow, and susceptibility to renewal, and renewal in the language in terms of style and grammar, in excavating in the treasures of the language and trying to employ its energies and capabilities. From this point of view, this research came to talk about translation, Arabization and borrowing within the limits of two topics, the first of which focused on the theoretical foundation of the scientific term, which was divided into two demands: The second topic was to talk about the ways of transferring the linguistic term (translation, Arabization and borrowing) divided into two demands: the first requirement was devoted to talking about translation and its impact on the development of terms, and the second requirement was to talk about Arabization and borrowing and their impact on the development of terms, followed by the conclusion of the research.